Protection behaviors and related factors against COVID-19 in the healthcare workers of the hospitals in Iran: A cross-sectional study - Reyhaneh Toghanian; Saeed Ghasemi; Meimanat Hosseini; Malihe Nasiri (Iranian Journal of Nursing and Midwifery Research, 2022)
Background: Protective behaviors play a key role in reducing the incidence of COVID-19 in HealthCare Workers (HCWs), and these behaviors are related to other factors. These related factors have not been comprehensively evaluated and determined in the literature. This study aimed to determine protection behaviors against COVID-19 and their related factors using the Protection Motivation Theory (PMT) among HCWs of hospitals in Tehran, Iran, in 2021. Materials and Methods: For this cross-sectional study, 270 HCWs of different wards in 3 hospitals in Tehran, Iran, were selected through multistage sampling (April to July 2021). The participants completed a self-reporting questionnaire which consisted of a demographic characteristics form and questions about protective behaviors against COVID-19 and other constructs of the PMT (60 items). Data analysis was performed using descriptive and inferential methods. Results: The mean score of the protective behaviors of the HCWs was 4.20 (SD = 0.56) and was significantly higher in the nurses, women, married individuals, and those with a BSc degree compared with others (p < 0.05). Furthermore, the results of multiple regression analysis showed that protection behavior among HCWs could be strongly predicted by the type of profession, protection motivation/intention, and self-efficacy constructs (F14, 255 = 16.34, p < 0.001). Conclusions: The protection behaviors of HCWs against COVID-19 were relatively desirable and these behaviors were related to and predicted by various factors. These results could apply to developing plans for protective behaviors against COVID-19 and possibly other infectious diseases among HCWs. Further research in this regard is recommended.